MoO3 subnanoclusters on ultrasmall mesoporous silica nanoparticles: an efficient catalyst for oxidative desulfurization. Issue 71 (19th September 2017) - Wang, Jiasheng; Wu, Wenpei; Ye, Hongyang; Zhao, Yahong; Wang, Wan-Hui; Bao, Ming
Abstract : MoO3 subnanoclusters encapsulated in ultrasmall mesoporous silica nanoparticles ( ca. 14 nm) exhibited enhanced catalytic activity for oxidative desulfurization. Abstract : Subnano-MoO3 supported on ultrasmall mesoporous silica nanoparticles (UMSN, ca. 14 nm) has been successfully synthesized by a reverse microemulsion method. The obtained subnano-MoO3 /UMSN exhibited superior catalytic activity for the oxidative desulfurization of model diesel. The dibenzothiophene can be oxidized to dibenzothiophene sulfone and removed simultaneously by adsorbing on the catalyst. The superiority in catalytic performance of subnano-MoO3 /UMSN can be attributed to the subnanometer size and the mesoporosity of the ultrasmall support. The origin of the unusual catalytic properties of the subnanoclusters was also explored preliminarily.